Anatomical Peculiarities of Reproductive Organs of «Lycopersicon esculentum» Infected with a Severe Strain of Tobacco Mosaic Virus - Sayed, El Sayed Tarek A.; Eskarous, Josephine; El Shamy, Magdy M. (Phytopathologia Mediterranea, 2000)
The histopathology of tomato sepals, petals, anthers, ovaries and fruit pericarps infected with a highlyheat resistant strain of TMV showed many peculiarities. Among these were: undulation and wrinkling of the lowerepidermis of sepals and petals, presence of isthmus and failure of xylem and phloem to differentiate. The epidermalcells of the anthers were hooked, the number of pollen sacs was reduced and the vascular elements of the lower regionof the fruits appeared thicker than normal, ruptured or disintegrated, and the cortical region appeared small with awavy or ruptured layers.